A Sociocognitive Discussion of Learning Resource Selection in Self-Directed Learning - Ponton, Michael K.; Dondlinger, Mary Jo (International Journal of Learning and Development, 2024)
An essential feature of social cognitive theory is its use of reciprocal determinism as a lens to understand any domain of human functioning. In this conception of personal agency, human development and activity is the result of the interaction of three constituent factors: person, behavior, and environment. One particular domain of functioning is self-directed learning that describes the process of an individual learner who acts as an agent to create and direct all aspects of a learning activity, which includes the critical function of selecting learning resources (i.e., critical because learning quality is the direct result of such choices). The purpose of this article is to use this sociocognitive model of reciprocal determinism as an interpretive framework for discussing how self-directed learners select learning resources.